Application of methods of marketing analysis for the increase of the activity of the wood processing company on the Latvian market - Tsaurkubule, Zhanna; Vishnevska, Alevtina (Zastosowanie metod analizy marketingowej do zwiększenia efektywności działalności przedsiębiorstwa przetwórstwa drewna na rynku łotewskim, 2018)
The article analyses the activity of the wood processing company on the Latvian market and shows the role of marketing research to improve the efficiency of the enterprise. It also examines issues, relating to forestry industry of Latvia, its development as the most important sector of the national economy and the situation with the export of timber. Marketing research of the consumer segment of woodworking firm is conducted, which is a member of five leaders of the wood processing industry in Latvia. With the help of modern methods of marketing analysis a group of the most profitable firms for customers and consumer’s preferences are identified. To this end a multivariate model of consumer opinions of Fishbein is used. Actions to improve the company’s product offering is made on the basis of the conducted analysis, which allowed the company to increase sales volumes and gain stronger competitive position on the market of wood processing of Latvia.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 536, s. 160-169
Keywords: Latvia; forestry; wood processing; marketing research; competitive analysis; Fishbein model; Łotwa; leśnictwo; przetwórstwo drewna; badania marketingowe; analiza konkurencji; model Fishbeina